A five-domain Kazal-type serine proteinase inhibitor from black tiger shrimp Penaeus monodon and its inhibitory activities - Nawarat Somprasong (2018)
A novel five-domain Kazal-type serine proteinase inhibitor, SPIPm2, identified from the hemocyte cDNA library of black tiger shrimp Penaeus monodon was successfully expressed in the Escherichia coli expression system. The expressed recombinant SPIPm2 (rSPIPm2) as inclusion bodies was solubilized with a sodium carbonate buffer, pH10, and purified by gel filtration chromatography. The molecular mass of rSPIPm2 was determined using MALDI-TOF mass spectrometry to be 29.065 kDa. The inhibitory activities of rSPIPm2 were tested against trypsin, α-chymotrypsin, subtilisin and elastase. The inhibitor exhibited potent inhibitory activities against subtilisin and elastase, weak inhibitory activity against trypsin, and did not inhibit chymotrypsin. Tight-binding inhibition assay suggested that the molar ratios of SPIPm2 to subtilisin and elastase were 1:2 and 1:1, respectively. The inhibition against subtilisin and elastase was a competitive type with inhibition constants (Ki) of 0.52 and 3.27 nM, respectively. The inhibitory activity of SPIPm2 against subtilisin implies that, in shrimp, it may function as a defense component against proteinases from pathogenic bacteria but the elastase inhibitory function is not known. © 2006 Elsevier Ltd. All rights reserved.